2018
DOI: 10.2147/ceor.s163829
|View full text |Cite|
|
Sign up to set email alerts
|

Budget impact analysis of sarilumab for the treatment of rheumatoid arthritis in patients with an inadequate response to conventional synthetic DMARD or TNF inhibitor therapies

Abstract: ObjectiveTo estimate the 5-year budget impact (BI) on a US health plan of introducing sarilumab – a human immunoglobulin G1 anti-IL-6 receptor α monoclonal antibody – as combination treatment with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) or monotherapy in patients with moderate-to-severe rheumatoid arthritis (RA).MethodsBI analysis was conducted from a commercial payer perspective. Treatment-eligible populations included adult patients with moderate-to-severe RA and inadequate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Two prior BIMs related to the TNFi-IR population were published before the availability of baricitinib. The first BIM estimated the 5-year budget impact of sarilumab to US healthcare commercial payers by considering a patient population with moderate-to-severe RA and IR to csDMARDs or TNFis [49]. Overall, the analysis found that sarilumab was cost saving with a lower treatment cost and consistent dosing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prior BIMs related to the TNFi-IR population were published before the availability of baricitinib. The first BIM estimated the 5-year budget impact of sarilumab to US healthcare commercial payers by considering a patient population with moderate-to-severe RA and IR to csDMARDs or TNFis [49]. Overall, the analysis found that sarilumab was cost saving with a lower treatment cost and consistent dosing.…”
Section: Discussionmentioning
confidence: 99%
“…First, AEs have not been found to be significant model drivers in previous RA health technology assessments and have sometimes been excluded given the assumption that there is no difference in the safety profiles of bDMARDs [48]. Second, a previously published BIM in RA excluded AEs due to heterogeneity in AE reporting [49]. Finally, even if AEs were included, the RA-BEACON trial results show that the impact would be low [6].…”
Section: Cost and Resource Usementioning
confidence: 99%
“…An annual RA prevalence rate of 0.5% 19 was applied to the hypothetical 1 million member health plan and estimated that 65.5% of RA patients had moderate-to-severe disease activity 20 . We estimated 88.4% of patients used disease-modifying antirheumatoid drug (DMARD) therapy 21 , of whom 39% received conventional synthetic DMARD (csDMARD) and 61% received non-csDMARD therapy 22 . We assumed that non-csDMARD patients had already started a biologic or JAKi therapy whereas patients with inadequate response to csDMARD (36.9% of users) 22 would switch to non-csDMARDs for the first time.…”
Section: Populationmentioning
confidence: 99%
“…We estimated 88.4% of patients used disease-modifying antirheumatoid drug (DMARD) therapy 21 , of whom 39% received conventional synthetic DMARD (csDMARD) and 61% received non-csDMARD therapy 22 . We assumed that non-csDMARD patients had already started a biologic or JAKi therapy whereas patients with inadequate response to csDMARD (36.9% of users) 22 would switch to non-csDMARDs for the first time. Thus, we estimated 12.7% of moderate-to-severe RA patients were initiating biologics or JAKi and 53.9% were experienced biologic or JAKi users.…”
Section: Populationmentioning
confidence: 99%